2005
DOI: 10.1159/000083446
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin’s Lymphomas in Greece according to the WHO Classification of Lymphoid Neoplasms

Abstract: The purpose of this retrospective study, the largest unselected series in our country, was to illustrate the clinicopathological features of non-Hodgkin’s lymphoma (NHL) classified according to the World Health Organization (WHO) classification of lymphoid neoplasms. A retrospective analysis was conducted and clinical features of histological subtypes were established in 810 patients (age ≧15 years) with NHL who were treated at 8 major centers representative of Greece. There were 435 males and 375 females 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 35 publications
(29 reference statements)
3
23
1
3
Order By: Relevance
“…33 (84.61%) of our cases had B cell lineage, 4 (10.25%) had T cell lineage and 2 (5.12%) of the cases belonged to miscellaneous group. The current study and similar reports from some of the surrounding Middle East countries as well as the West show a low relative proportion of T-cell lymphomas (Naresh et al, 2004;Economopoulos et al, 2005). It was claimed that non Hodgkin lymphoma, occurring in adolescence was an independent risk factor for a poorer prognosis compared with that occurring in children younger than 15 years of age (Cairo et al, 2003).…”
Section: Discussionsupporting
confidence: 75%
“…33 (84.61%) of our cases had B cell lineage, 4 (10.25%) had T cell lineage and 2 (5.12%) of the cases belonged to miscellaneous group. The current study and similar reports from some of the surrounding Middle East countries as well as the West show a low relative proportion of T-cell lymphomas (Naresh et al, 2004;Economopoulos et al, 2005). It was claimed that non Hodgkin lymphoma, occurring in adolescence was an independent risk factor for a poorer prognosis compared with that occurring in children younger than 15 years of age (Cairo et al, 2003).…”
Section: Discussionsupporting
confidence: 75%
“…[3] The current study and similar reports from some of the surrounding Middle East countries as well as the West show a low relative proportion of T-cell lymphomas. [2,8,21,22,30,31,35] This is in contrast to its high proportion in Far Eastern countries like Japan, China, and Korea were it constitutes 27−30.5% of NHL, [4,5,36] and to a lesser extent the 15-18% reported from India. [27,28] Such significant variation in the geographical distribution of T-cell lymphomas has long been recognized and has been attributed to racial predisposition, HTLV-I viral infection and lower relative incidence of B-cell NHL in the Far East.…”
Section: Discussionmentioning
confidence: 98%
“…[1] Studies from Western Europe, North America, Japan, China, India, and some Middle Eastern countries have revealed that the relative proportions of various ML as determined by this classification differs with geographical region. [1][2][3][4][5][6][7][8] ML is the third most common reported malignancy in Iraq, [9] but there are few published Iraqi studies on the subject [10][11][12][13][14] and none have addressed the relative distribution of the various subtypes based upon the WHO classification. This study was undertaken in order to determine the types of ML occurring in the country as based upon the WHO updated classification [15,16] and to compare the distribution of diagnoses with published studies from nearby Middle Eastern countries as well as other developed and underdeveloped regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Male dominancy rates differed among countries (USA, 1.43; Europe. 1.23: Austria, 1.52; Greece 1.16, and Korea, 1.6 [8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%